Second‐Generation Non‐Covalent NAAA Inhibitors are Protective in a Model of Multiple Sclerosis. (12th July 2016) - Migliore, Marco; Pontis, Silvia; Fuentes de Arriba, Angel Luis; Realini, Natalia; Torrente, Esther; Armirotti, Andrea; Romeo, Elisa; Di Martino, Simona; Russo, Debora; Pizzirani, Daniela; Summa, Maria; Lanfranco, Massimiliano; et al.
Abstract: Palmitoylethanolamide (PEA) and oleoylethanolamide (OEA) are endogenous lipid mediators that suppress inflammation. Their actions are terminated by the intracellular cysteine amidase, N ‐acylethanolamine acid amidase (NAAA). Even though NAAA may offer a new target for anti‐inflammatory therapy, the lipid‐like structures and reactive warheads of current NAAA inhibitors limit the use of these agents as oral drugs. A series of novel benzothiazole–piperazine derivatives that inhibit NAAA in a potent and selective manner by a non‐covalent mechanism are described. A prototype member of this class (8 ) displays high oral bioavailability, access to the central nervous system (CNS), and strong activity in a mouse model of multiple sclerosis (MS). This compound exemplifies a second generation of non‐covalent NAAA inhibitors that may be useful in the treatment of MS and other chronic CNS disorders.